A Bruch's membrane substitute fabricated from silk fibroin supports the function of retinal pigment epithelial cells in vitro. (9th October 2015) - Shadforth, Audra M. A.; Suzuki, Shuko; Theodoropoulos, Christina; Richardson, Neil A.; Chirila, Traian V.; Harkin, Damien G.
Abstract: Silk fibroin provides a promising biomaterial for ocular tissue reconstruction, including the damaged outer blood–retinal barrier of patients afflicted with age‐related macular degeneration (AMD). The aim of the present study was to evaluate the function of retinal pigment epithelial (RPE) cells in vitro, when grown on fibroin membranes manufactured to a thickness similar to that of Bruch's membrane (3 µm). Confluent cultures of RPE cells (ARPE‐19) were established on fibroin membranes and maintained under conditions designed to promote maturation over 4 months. Control cultures were grown on polyester cell culture well inserts (Transwell ® ). Cultures established on either material developed a cobblestone morphology, with partial pigmentation, within 12 weeks. Immunocytochemistry at 16 weeks revealed a similar distribution pattern between cultures for F‐actin, ZO‐1, ezrin, cytokeratin pair 8/18, RPE‐65 and Na + /K + ‐ATPase. Electron microscopy revealed that cultures grown on fibroin displayed a rounder apical surface with a more dense distribution of microvilli. Both cultures avidly ingested fluorescent microspheres coated with vitronectin and bovine serum albumin (BSA), but not controls coated with BSA alone. VEGF and PEDF were detected in the conditioned media collected from above and below the two membrane types. Levels of PEDF were significantly higher than for VEGF on both membranes and a trend was observed towards larger amounts of PEDF in apical compartments. These findings demonstrated that RPE cell functions on fibroin membranes are equivalent to those observed for standard test materials (polyester membranes). As such, these studies support advancement to studies of RPE cell implantation on fibroin membranes in a preclinical model. Copyright © 2015 John Wiley & Sons, Ltd.